Implantación del sistema de contabilidad en la empresa tienda musical Loja, período febrero–abril/2015 - Valladares Solano, Lucía Katherine (2016)
This thesis called "IMPLEMENTATION OF ACCOUNTING SYSTEM IN THE COMPANY STORE MUSICAL LOJA, PERIOD FEBRUARY-APRIL/2015" it made in order to educate the owner about the importance of implementing an accounting system and report the situation economic actual financial thereof. To carry out this work was necessary to apply methods such as scientific, deductive, inductive, analytic and synthetic techniques and direct observation, bibliography and interview; allowing comply with each of the specific objectives, analyze and interpret the results for the efficient development of the thesis. First, the physical realization of inventories of securities, rights assets and liabilities of the company under study, eager to know the belongings of the business, make invoice information purchases and sales will becollected during the months of February to April 2015. The second target will be proceeded to lift its inventory of merchandise through the perpetual inventory system perpetual inventory or specifically kardex cards, which helped to know exactly the existing merchandise in the company. In the third objective main and auxiliary accounts in accordance with the requirements of commercial, for greater control of its operations, whose data were the basis for the preparation of financial statements was designed. The fourth objective the accounting process, developed for this chart of accounts according to the activities that the company was executed; being necessary to codify and define each account, expressed through manual analysis, then the assets, securities held by the commercial information, which served as a starting point for the preparation of the Inventory and State Initial Situation were detailed. With the information in the purchase invoices and sales, he developed the journal, whose seats were duly mayorizados, in order to build the Balance, Worksheet and finally the financial statement. With the development of this research, it can fully meet the economic and financial situation of the Musical Loja Shop, real information, which enable the owner to take the necessary corrective measures for attaining greater optimization of business resources.